PSIII-5 Metabolic hormones, live weight, grazing behaviour and offspring distance of primiparous beef cows grazing grasslands at two herbage allowances. (5th December 2019) - Claramunt, Martin; Meikle, Ana; Soca, Pablo
Abstract: The objective of this study was to evaluate the effect of herbage allowance (HA; herbage mass in kg DM/ha: stocking rate in kg LW/ha ratio) during gestation and lactation on cow and calf LW, body condition score (BCS), insulin, IGF-1, and leptin concentrations, daily grazing, ruminating and idling proportion cow-calf distance in primiparous beef cows from -10 to 70 days from temporary suckling restriction (nose plates on calves during 12 days=TW; day 0=initiation of TW at 86 ± 10 postpartum) and flushing (2 kg FB/cow/day whole-rice bran for 22 days). Thirty-three cows were allocated to HA treatments during gestation and lactation (-150 to 195 days relative to calving), that annually averaged 2.5 (low HA) and 4 kg DM/kg LW (high HA). Data were analyzed using mixed models with repeated measures and general linear mixed models. Cows LW and BCS did not differ during the -10 to 50 day period but were greater in high HA at the end of the study. Concentrations of IGF-I were greater in high HA (80 vs 70 ± 3 ng/mL), but insulin and leptin did not differ. Daily grazing proportion was lower in high HA (0.64 vs 0.68 ± 0.06; P < 0.05), and the opposite occur with rumination and idling (P < 0.05). Cow-calf distance was greater in low HA cows (0.57 vs 0.75 ± 0.006; P < 0.05) and increased greatly in this group after flushing. Milk yield was greater (3.7 vs 3 ± 0.3; P > 0.05) and calf weight did not differ between treatments from -10 to 35 day and was greater after 45 days in high HA compared to low HA. Thus, increasing HA resulted in greater IGF-1 concentrations and milk yield, and induced changes in grazing and maternal behavior that were associated with increased cow and calf LW and BCS.